2022
DOI: 10.1371/journal.pone.0274823
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer bioinformatic analysis of the carcinogenic role of SMARCA1 in human carcinomas

Abstract: SMARCA1is a mammalian imitation switch (ISWI) gene that encodes for SNF2L. SNF2L is involved in regulating cell transition from a committed progenitor state to a differentiated state. Although many papers have detailed the correlation between SMARCA1 and different cancers, no pan-cancer analysis has been conducted to date. We started by exploring the potential carcinogenic role of SMARCA1 across 33 carcinomas using the cancer genome atlas (TCGA) and the genotype-tissue expression (GTEx) databases. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…PAWR known as Par-4, this gene has been associated with major depressive disorder. Genetic variations in PAWR have been found to be related to susceptibility to major depressive disorder, but not to the response to antidepressant treatment [ 24 ]. PSIP1 encodes a protein that is involved in transcriptional regulation and chromatin remodeling, suggesting potential roles in gene expression regulation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAWR known as Par-4, this gene has been associated with major depressive disorder. Genetic variations in PAWR have been found to be related to susceptibility to major depressive disorder, but not to the response to antidepressant treatment [ 24 ]. PSIP1 encodes a protein that is involved in transcriptional regulation and chromatin remodeling, suggesting potential roles in gene expression regulation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in PAWR have been found to be related to susceptibility to major depressive disorder, but not to the response to antidepressant treatment. 24 PSIP1 encodes a protein that is involved in transcriptional regulation and chromatin remodeling, suggesting potential roles in gene expression regulation. 25 It is important to note that further research is needed to elucidate the specific functions and potential involvement of these genes in CRC and colorectal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Sangerbox database 3.0 ( http://vip.sangerbox.com ) [ 41 43 ], which integrates multiple databases and processes data in batches, is a user-friendly bioinformatic platform that provides numerous interactive analyses. The potential relationships between GLS expression and immune cell infiltration in pan-cancer were evaluated using this platform.…”
Section: Methodsmentioning
confidence: 99%
“…FAM99A gene, which codes for an lncRNA, had a lower expression in TGCT compared with normal tissue of the GTEx database; however, further investigations found a positive correlation with four methylation probe sites, and no prognostic value was considered for this cancer type, given the limitations of the study [62]. Interesting results were also obtained in a study on SMARCA1, a gene that encodes for a chromatin remodeling protein, which only evaluated its expression and DNA methylation due to limited data [74]. Despite low levels of expression, when looking at DNA methylation levels, the authors found two CpG sites in the promoter region that were negatively correlated with expression and another two CpG sites outside the promoter region with a positive association with expression [74].…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 99%
“…Interesting results were also obtained in a study on SMARCA1, a gene that encodes for a chromatin remodeling protein, which only evaluated its expression and DNA methylation due to limited data [74]. Despite low levels of expression, when looking at DNA methylation levels, the authors found two CpG sites in the promoter region that were negatively correlated with expression and another two CpG sites outside the promoter region with a positive association with expression [74].…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 99%